Single-domain antibody C7b for address delivery of nanoparticles to HER2-positive cancers - Vorotnikov, Yuri A; Novikova, Evgeniya D; Solovieva, Anastasiya O; Shanshin, Daniil V; Tsygankova, Alphiya R; Shcherbakov, Dmitrii N; Efremova, Olga A; Shestopalov, Michael A (Nanoscale, 2020)
Monoclonal antibodies (mAb) demonstrate great potential as immunotherapy agents for the treatment of diseases such as cancer as well as tagging for the targeted delivery of multicomponent therapeutic or diagnostic systems. Nevertheless, the large physical size, poor stability of mAbs and abnormal allergic reactions still remain the main issues affecting their generalised use. Single-domain antibodies (sdAb) are seen as the next generation of antibody derived therapeutics and diagnostics. This work presents the optimised production method for HER2-specific sdAb C7b, which led to an ∼11-fold increase in protein yield. In addition, the in vitro and in vivo efficiencies of the targeted delivery of a model nanoparticle cargo (50 nm silica particles doped with Mo 6 phosphorescent clusters) conjugated to C7b against those conjugated to HER2-specific trastuzumab is benchmarked. Specifically, this paper demonstrates the significantly higher rate of accumulation in and excretion from xenograft cancer tissue of nanoparticles with C7b, which is of particular importance for diagnostics, i.e. delivery of imaging agents. Single-domain antibody C7b is benchmarked against trastuzumab for targeted delivery of photoactive silica nanoparticles to a HER2 overexpressing cancer cell line and tissue.